2017
DOI: 10.5294/pebi.2017.21.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Formación bioética e intercultural en enfermería: revisión temática

Abstract: ReSUmenObjetivo: analizar las tendencias de la formación bioética e intercultural en los programas de enfermería, y establecer los aspectos que deben contemplarse para mejorar la formación. Materiales y método: búsqueda de información en bases de datos científicas de acceso libre y repositorios de tesis doctorales de universidades; se utilizaron las palabras clave: "Bioética", "Educación", "Formación", "Enfermería", "Cultura", en español e inglés. No se establecen límites según la fecha de publicación. Resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
1
0
3
Order By: Relevance
“…An existing barrier highlighted by previous research is that the vast majority of the training provided at different academic levels in relation to this topic is theoretical, as it can be also verified in the results of this scoping review and in other studies carried out [68]; however, there are studies that reveal that training in clinical practice is the most effective for developing knowledge, awareness, and safety among students [36]. Thus, Latin American nursing professionals have training that seems to be detached from professional practice, and this is contrary to what is necessary to train a professional, capable of acting and making real changes in their care practice [69]. Other forms of teaching, like exchanges between nursing students from different studies, have had positive results in the acquisition of cultural competence in Spain [40], coinciding with studies carried out in other countries such as one that took place among students from two universities, one from the US and the other from Thailand, where it was revealed that the experience was effective for students to gain confidence, increase their knowledge of different cultures as well as their cultural competence [58].…”
Section: Discussionsupporting
confidence: 62%
“…An existing barrier highlighted by previous research is that the vast majority of the training provided at different academic levels in relation to this topic is theoretical, as it can be also verified in the results of this scoping review and in other studies carried out [68]; however, there are studies that reveal that training in clinical practice is the most effective for developing knowledge, awareness, and safety among students [36]. Thus, Latin American nursing professionals have training that seems to be detached from professional practice, and this is contrary to what is necessary to train a professional, capable of acting and making real changes in their care practice [69]. Other forms of teaching, like exchanges between nursing students from different studies, have had positive results in the acquisition of cultural competence in Spain [40], coinciding with studies carried out in other countries such as one that took place among students from two universities, one from the US and the other from Thailand, where it was revealed that the experience was effective for students to gain confidence, increase their knowledge of different cultures as well as their cultural competence [58].…”
Section: Discussionsupporting
confidence: 62%
“…Los profesionales sanitarios están llamados a brindar una atención que promueva la protección de los derechos y la calidad de vida de los pacientes, para lo cual es necesario reforzar sus conocimientos, al igual que otras competencias como la identificación de aspectos morales, la toma de decisiones, la motivación (10,11,31,32) y la sensibilidad frente al sufrimiento del otro (38). Morocho (2), desde Harrysing et al (2004), menciona que, debido a la importancia del tema, se incorporó la enseñanza-aprendizaje en las carreras de Ciencias de la Salud en América Latina durante los años ochenta, por cuanto este colectivo es el mayor grupo de profesionales que conforman las unidades operativas en todos los niveles de salud de todos los países del mundo.…”
Section: Educación Y Formación En Bioéticaunclassified
“…Para diferentes autores, el docente constituye un modelo de actuación profesional que influye en el estudiante y opera como intermediario entre el conocimiento formal y los marcos cognitivos, culturales y afectivos del educando. Los valores, la postura ideológica y el ejemplo del docente se van a reflejar en el futuro profesional, por tanto, se asumen como actores importantes en la formación ética del enfermero, principalmente si consideran la vida cotidiana, académica y asistencial como espacios de formación (11,21,22). Cubas (21) manifiesta que "el docente universitario debe tener ciertas características que le ayuden a ser modelo a imitar, no solo por su sapiencia científica, y, especialmente, por su vocación como persona llamada a servir a los demás" (21, p. 47).…”
Section: La Formación En Bioética En Enfermeríaunclassified
“…Likewise, for the academic training of the nursing professional, models and theories are taken into account for the development of teaching-learning, such as scientific studies conducted by Leininger and his cultural nursing care of diversity and universality, who argues that nursing differs from other disciplines, by the care activities based on culture, knowledge of scientific care and social relationship skills (Fernandes et al,2018;Pucheu, 2018). Likewise, Campinha-Bacote, in her model of cultural competence, mentions that they are acquired through the availability and skills to develop effective work within the cultural context of a community, family, and individual (Valdez-Fernández, 2017). Finally, Spector and his model of cultural heritage and health traditions assume the importance of tradition in the health of individuals, as well as in the behaviors related to health and disease (Bada, 2021;Olivera, 2019).…”
Section: Introductionmentioning
confidence: 99%